Simultaneous Hepatic and Mesenteric Hydatid Disease—A Case Report - Paramythiotis, Daniel; Karakatsanis, Anestis; Bangeas, Petros; Kofina, Konstantinia; Papadopoulos, Vassileios; Apostolidis, Stylianos; Michalopoulos, Antonios (Frontiers in Surgery, 2017)
Introduction: Hydatid cysts most commonly present in the liver and the lungs, however, they can appear more rarely in other locations, such as the mesentery, with a rather unclear mechanism of manifestation. Herein we present a case of simultaneous presence of hydatid cysts in the liver and the mesentery of a young man. Case Report: A 39-year-old man was referred to our Department for further investigation of intermittent abdominal pain, especially in the right upper quadrant, and abdominal distension. Abdominal CT imaging revealed three calcified lesions, one in the liver, a similar adjacent to an ileal loop and one close to the urinary bladder, while antibody control was positive for echinococcal infection. The lesions were excised and the patient was discharged on the 7th postoperative day in good general condition. Post-operative control after six months did not show any signs of recurrence. Conclusion: Simultaneous presence of hydatid cysts in two organs occurs in 5-13% of cases. Presence in the mesentery is extremely rare, although, should be included in the classic differential diagnosis, especially in endemic areas.